2019
DOI: 10.1002/qua.26016
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Estrada index and π‐electronic energies for benzenoid hydrocarbons with applications to boron nanotubes

Abstract: In this article, we present an efficient computer-based computational technique to compute the energy and Estrada index of graphs. It is shown that our computational method is more efficient and bears less computational and algorithmic complexity. We use our method to show the main result of this article, which asserts that the Estrada index correlates with the π-electronic energies of lower benzenoid hydrocarbons with correlation coefficient 0.9993. This enhances the practical applicability of the Estrada ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…In this work, further we discuss QSPR analysis of said topological indices. We also show that the characteristics obtained are highly correlated with the characteristics of anticancer drugs using linear regression [4,5,6,7,8,9].…”
Section: Introduction and Terminologiesmentioning
confidence: 67%
See 1 more Smart Citation
“…In this work, further we discuss QSPR analysis of said topological indices. We also show that the characteristics obtained are highly correlated with the characteristics of anticancer drugs using linear regression [4,5,6,7,8,9].…”
Section: Introduction and Terminologiesmentioning
confidence: 67%
“…Hence it can be remarked that all the physical and chemical properties of anticancer drugs are positively correlate with the defined degree based topological indices. Tables 5,6,7,8,9,10,11,12,13,14,15,16,and 17 shows the regression model of various physico-chemical properties. It can be observed that the regression model value r is more than 0.6 and p value shows less than 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Hayat et al [43] extended the method in [41] to the class of degree-distance-based and degree-based descriptors. Hayat et al [44] presented a similar technique to compute the adjacency energy, the adjacency Estrada index and the inertia indices. In this paper, we extend the technique of Hayat et al [44] to the 33 spectrum-based topological descriptors in Section II.…”
Section: Methodsmentioning
confidence: 99%
“…Following the seminal paper on these topics in [15], [44], [64], we use 30 lower benzenoid hydrocarbons which are in fact the 30 lower PAHs to access the prediction ability of a distance-based spectral descriptor. Correlation ability with the π-electronic energy was first studied with the adjacency energy of a graph by Gutman [34].…”
Section: Predictive Potential Of Distance-based Spectral Descriptors For Determining the π-Electronic Energymentioning
confidence: 99%
“…where d u denotes the degree of the vertex u and sum runs over all edges uv of G. ere are many topological indices which appeared in the literature of mathematical chemistry (see for example [9][10][11][12][13]). Among the degree-based topological descriptors, the most studied are the first and second Zagreb indices [14][15][16][17], the sum-connectivity index [17][18][19], the atom-bond connectivity index [17,20], the augmented Zagreb index [17,21,22], the geometric arithmetic index [23][24][25], and the harmonic index [19,26,27].…”
Section: Introductionmentioning
confidence: 99%